The Enhancement of Production and Marketing of Cricket Farming Quality Business During Covid-19 Pandemic in Sudimara Village, Bali - I Gede Cahyadi Putra; I Made Tamba; Ni Made Indah Rinita Santi (Journal of the Community Development in Asia (JCDA), 2021)
This study carried out in the cricket farming business in Sudimara Village, Tabanan, Bali. The purpose of this study is to help mintra in preventing Covid-19, to manage the production and marketing processes of cricket business in order to generate increased sales turnover during the Covid-19 pandemic. The method of this study was carried out by making prior observations about partner activity units. After that, mapping the problem in order to find the solution. After the activities were carried out, there was an increase in the quality of production and promotion, additional cages were available that could increase the yield of crickets, and business owners had understood how to use and maintain social media Facebook and Instagram and were able to operate them.